Challenges and Best Practices of Teaching and Learning among Islamic Education Teachers during the COVID-19 Pandemic in Malaysia - Zetty Nurzuliana Rashed; Nurul Rahimah Binti Mohd. Hanipah (International Journal of Pedagogy and Teacher Education, 2021)
Online learning (e-learning) has become a norm since the Covid-19 pandemic struck the world. The global health crisis has forced teachers and students to drastically adapt to a new method of teaching and facilitation (PDPC), i.e. online. However, teachers living in rural areas face various challenges teaching online due to poor Internet access. There are still many teachers who are less skilled in information technology to deliver teaching materials online. This study uses a qualitative approach by interviewing three secondary school Islamic Education teachers as the study participants. The findings reveal that the teachers utilise social media such as WhatsApp and Telegram to convey various information, instructions and training. The learning mediums used also vary, from the Zoom app to Google Meet and video calls. In addition, teachers employ other online learning tools such as Google Classroom. Teachers also employ flexible online teaching and learning schedules to overcome issues such as parents who have many school-going children but lack the funds to purchase gadgets for each child. A flexible schedule enhances online learning as the school-going children in each household can use devices but not simultaneously. Other major challenges include students’ lack of cooperation (whether in an online or offline class) and the failure of parents to monitor their children’s progress. As a result, educators need to be more creative and ready to acquire new skills to meet the current challenges. Educators need to adapt online teaching and learning methods in line with the concept of 21st Century Learning (PAK21). Therefore, the use of appropriate and creative technology in a remote learning environment encourages students to focus on learning and prevents dropouts.